Family polyposis of the colon: diagnosis - Viola Núñez, Humberto; Quadrelli, Roberto; Marabotto, Nelson (Cirugía del Uruguay, 1985)
Basad on six cases treated, we present our experience in the diagnosis of family polyposis of the colon, a hereditary disease with a tendency to early malignant degeneration.